2018
DOI: 10.1111/1752-1688.12675
|View full text |Cite
|
Sign up to set email alerts
|

Meadow Restoration Increases Baseflow and Groundwater Storage in the Sierra Nevada Mountains of California

Abstract: We discuss a recent paper which evaluated the hydrologic changes resulting from a pond-and-plug meadow restoration project in the Sierra Nevada Mountains of California. In the study, measurements of streamflow into and out of the meadow suggested late-summer baseflow increased as much as five-fold when compared with prerestoration conditions. However, the volume of streamflow attributed to the restored meadow (49,000-96,000 m 3 over four months) would require that 2.5-4.8 m of saturated meadow soils drain duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The restoration project described in this paper encompassed a 0.1 km 2 (100,000 m 2 ) wet meadow in which soils were mapped as silt‐loams (Soil Survey Staff ). Prior to restoration in 2012 the streamflow attributed to meadow drainage was 7,000 m 3 (table 1, Hunt et al ), or approximately 0.07 m of free liquid water over the 100,000 m 2 area which, with a 20% drainable porosity, would be accounted for by a 0.35 m change in the water table. The prerestoration well data (figure 5, Hunt et al ) indicate that the typical change in water table depth from June to October was approximately 0.2 m, with a maximum change in approximately 0.5 m (i.e., well 5, prerestoration, figure 5, Hunt et al ) and thus the reported changes in streamflow are generally consistent with the reported change in the water table elevation over the summer assuming no plant use, which gives confidence in our estimate of drainable porosity.…”
Section: Evaluating Groundwater Data and Potential Streamflow Contribmentioning
confidence: 99%
See 4 more Smart Citations
“…The restoration project described in this paper encompassed a 0.1 km 2 (100,000 m 2 ) wet meadow in which soils were mapped as silt‐loams (Soil Survey Staff ). Prior to restoration in 2012 the streamflow attributed to meadow drainage was 7,000 m 3 (table 1, Hunt et al ), or approximately 0.07 m of free liquid water over the 100,000 m 2 area which, with a 20% drainable porosity, would be accounted for by a 0.35 m change in the water table. The prerestoration well data (figure 5, Hunt et al ) indicate that the typical change in water table depth from June to October was approximately 0.2 m, with a maximum change in approximately 0.5 m (i.e., well 5, prerestoration, figure 5, Hunt et al ) and thus the reported changes in streamflow are generally consistent with the reported change in the water table elevation over the summer assuming no plant use, which gives confidence in our estimate of drainable porosity.…”
Section: Evaluating Groundwater Data and Potential Streamflow Contribmentioning
confidence: 99%
“…Following restoration, the authors report that 49,000–96,000 m 3 of water drained from the meadow in 2013 and 2014, respectively (table 1, Hunt et al ). This amounts to approximately 0.49–0.96 m of free liquid water over the 100,000 m 2 area which, when stored in soils with a 20% drainable porosity, would be accounted for by a 2.5–4.8 m change in the water table.…”
Section: Evaluating Groundwater Data and Potential Streamflow Contribmentioning
confidence: 99%
See 3 more Smart Citations